Energy analysis and modelling in markal - K, Balachandran (2010)
The Asia-Pacific Economic Cooperation’s (APEC) 2009 publication on the energy demand and supply outlook forecasts Singapore’s energy demand to rise at an annual rate of 2.2 percent. From the period of 2005 till 2030, Singapore’s energy demand is expected to rise by as much as 72 percent. Moreover the industrial sector energy demand is expected to grow annually at an average rate of 4 percent. This study is about analysing the energy use pattern of Singapore, forecasting the energy requirement up to 2032 and looking at the various industrial sector end-use demand and investment and operating and maintenance cost.